DOCKING STUDIES OF CURCUMIN AS A POTENTIAL LEAD COMPOUND TO DEVELOP NOVEL DIPEPTYDYL PEPTIDASE-4 INHIBITORS - Enade Perdana Istyastono (Indonesian Journal of Chemistry, 2009)
Interaction of curcumin to dipeptydyl peptidase-4 (DPP-4) has been studied by employing docking method using Molecular Operating Environment (MOE) and AutoDock as the docking software applications. Although MOE can sample more conformational spaces that represent the original interaction poses than AutoDock, both softwares serve as valid and acceptable docking applications to study the interactions of small compound to DPP-4. The calculated free energy of binding (DGbinding)results from MOE and AutoDock shows that curcumin is needed to be optimized to reach similar or better DGbinding compare to the reference compound. Curcumin can be considered as a good lead compound in the development of new DPP-4 inhibitor. The results of these studies can serve as an initial effort of the further study.